Assessment of soil health parameters and application of the sustainability index to fields under conservation agriculture for 3, 6, and 9 years in India. Issue 12 (December 2020) - Bhattacharya, Priya; Maity, Pragati Pramanik; Mowrer, Jake; Maity, Aniruddha; Ray, Mrinmoy; Das, Shrila; Chakrabarti, Bidisha; Ghosh, Tridiv; Krishnan, P.
Abstract: The effect of duration of conservation agriculture adoption on soil carbon dynamics and system sustainability was evaluated on farms of 30 villages in the Nilokheri block of Karnal district, Haryana, India. Sustainability was evaluated, in which a number of soil physical, chemical, and biological parameters were measured and a Sustainability Index (SI) was applied. Soil samples were collected from existing conservation agriculture (CA) and conventional tillage (CT) farms. Villages under CA practices were subdivided as CA3, CA6, and CA9 based on the number of years of CA practice adoption. Results showed that bulk density (BD) of 0-15 cm soil depth was 7% greater in CA3 plots, whereas in CA6 and CA9 plots BD values were only 2% and 3% higher than CT. Soil organic carbon (SOC) in 0-15 cm soil depth was found to be greater by 16.32% in CA3 than CT plots, whereas SOC was higher by 38.77% and 61.22% in CA6 and CA9. In CA, for the 0–15 and 15-30 cm soil depths, labile pools were 36% and 22% greater than CT, respectively. For both the soil depths in CA, the recalcitrant pool was 12% and 9% more than CT, respectively. Microbial biomass carbon (MBC) values of the 0-15 cm soil depth were increased over CT by 18.57%, 47.08%, and 71.5% for CA3, CA6, and CA9 respectively. In CA plots, the SI of 0-15 cm soil depth ranged between cumulative ratings (CR) of 18–21, which indicates that CA practice is "sustainable" for both soil depths. For CT, CR ranged from 25 to 30 for both soil depths resulting in a SI of "sustainability with high input". Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) scores showed that SOC had the maximum weight (0.96) towards sustainability, giving it a rank of 1. Effective rooting depth (ERD), BD, texture, and wilting point (WP) ranked 2, 3, 4 and 5, respectively, indicating their corresponding weight of contribution towards the SI. Farmers in the Karnal district should be encouraged to adopt CA practices as they can increase SOC and move the systems from "sustainable with high input" to "sustainable". Abstract : Aggregation; Conventional agriculture; Glomalin content; Microbial biomass carbon; Soil organic carbon; TOPSIS; Agricultural soil science; Agronomy; Soil health; Soil quality; Environmental assessment.